Istikhdām Aflām al-Rusūm al-Mutaharrikah Qanāt Youtube “Marhaban Academy” fī Ta’līm al-Lughah al-Arabiyah ladā Thullāb al-Saf al-Sābi’ bi al-Madrasah al-Sanawiyah - Nasution, Zulkifli Nasution; Zein, Achyar (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2024)
Purpose- The purpose of this study is to find out the effectiveness of using the animated cartoon film YouTube channel